USE OF NEW METHODS IN MATHEMATICAL EDUCATION - Bekbauova, А.У.; Talipova, М.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article discusses the use of CLIL (Content and Language Integrated Learning) technologies in teaching the discipline "Differential Equations" in trilingual groups and in teaching of Algebra of the 8th grade in secondary schools. Currently, educational institutions and universities of Kazakhstan are actively implementing a program of modernization of the education system with transition to a trilingual system. CLIL learning technology is gaining popularity all over the world as a new curriculum for learning an additional language. The use of CLIL learning technology improves learning environment of students, reduces learning time, and also makes the learning concept broader and deeper. The article provides examples of some basic organizational work for the correct application of CLIL technologies in the discipline "Differential Еquations" for trilingual groups, examples of independent work for students are given. In order to determine the effectiveness of CLIL technology, which is one of the new methods in mathematical education, a survey was conducted among teachers of secondary schools in Aktobe, as well as graduates of Aktobe Regional University named after K. Zhubanov and the results of the survey were analyzed. In conclusion, it turned out that the new technique gives positive results in mathematical education.